Bench cutting tests and analysis for harvesting hemp stalk - Cheng, Shen; Bin, Zhang; Xianwang, Li; Guodong, Yin; Qiaomin, Chen; Chunhua, Xia (International Journal of Agricultural and Biological Engineering, 2017)
As a study basis in the field of design and research of harvester prototype, bench cutting test is to provide best parameters for the cutter design. In order to obtain the optimal parameters of cutter of the hemp harvester, cutting tests on hemp stalk were conducted to examine the influences of different geometrical parameters (length and edge type) of blade, different cutting speeds and stalk feeding speeds of reciprocating single movable blade and reciprocating double movable blades on the cutting performances (cutting power, cutting quality and synthesis score) by using self-designed test bench. According to features of different test factors, multi-factors orthogonal test was applied to determine the best combination of blade length, blade edge type and number of movable blade. Then with these parameters fixed, the optimal parameters for the factors of cutting speed and stalk feeding speed were obtained by quadratic-regression rotatable orthogonal test. According to the test results, the best combination of hemp stalk cutting was that using cutter with reciprocating double movable blades of long (120 mm) and serrated-edge at cutting speed of 1.1704 m/s and stalk feeding speed of 0.7079 m/s. The tests and analysis results can be applied into subsequent related researches on hemp harvesters. Keywords: hemp stalk, hemp harvester, blade, bench cutting test, cutter design DOI: 10.25165/j.ijabe.20171006.3475 Citation: Shen C, Zhang B, Li X W, Yin G D, Chen Q M, Xia C H. Bench cutting tests and analysis for harvesting hemp stalk. Int J Agric & Biol Eng, 2017; 10(6): 56–67.